Poetry Translation Of “Kamus Kecil” By Joko Pinurbo From English-Indonesian: Semantic Analysis of Literary Works - Gheta, Hermawan (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
Poetry is a literary work that often invites readers to think deeply first to find the true meaning delivered. This research explored the meaning of poetry which was transferred through the translation process from Indonesian to English seen from the semantic meaning in both source and target languages. The aim of this research was to analyze how the semantic meaning in poetry could be maintained and adjusted in the translation process. Data were obtained from the poem